Problems commercialization of rights to objects of intellectual property - Baranov, P.; Kosinska, O. (Problems of Engineer-Pedagogical Education, 2018)
The article draws attention to the need to develop methods for choosing optimal method commercialization of intellectual property. The authors examined the main approaches to the definition of the commercialization of intellectual property. Analyzes modern methods of commercialization, disclosed their nature, content, advantages and disadvantages of each. The use qualimetric approach in determining the best way to commercialization, which is based on a quantitative method of assessing quality indicators. Referred to in Article model is subjective, considers the indicative list of indicators, which can hold selection mode commercialization This method makes it possible to quantitatively compare the value of different methods of commercialization, given the different intellectual property rights and to choose the method more effective commercialization and short-lived. This technique in the vast majority can be applied to objects of industrial property, but it is possible also to use it for copyright, such as database, software and more.